“Application of International Environmental Laws regarding the Use of International Waterways: the Palestinian-Israeli Conflict” - Zuckerberg, Joaquin (Frónesis, 1970)
Among other issues being disputed currently within the Israeli-Palestinian conflict is the matter of water and the legal right of each party to access the scarce resources available in the region. Specifically, the question of which side holds a claim to the water of the West Bank Mountain and Gaza Aquifer must be addressed if an effective agreement is to be reached between the parties. This paper addresses the manner in which principles of international law dealing with international shared watercourses may help resolve the parties”™ water rights. Specifically, the paper analyses the legal principles which guide international water basins and the emerging doctrines of “significant harm” and “reasonable and equitable use” in the context of underground shared water. The paper finally attempts to provide some outlines which may provide a basis for a future settlement between Israel and any Palestinian legal entity which may arise as a consequence of a final or temporary agreement over the West Bank and Gaza territories.